Necessity and Desire: A Legal Conflict in Digital Age - Dr. Jayanta Ghosh (International Journal of Advanced Science and Technology, 2020)
In this digital age, selection of item according to necessity and the desire to use the sophisticated item is really a contradictory issue instead of a basic requirement. The necessity to use the item according to the desire depends upon lifestyle and choices of affordability in this developing economy. The ethical dilemma to use and non-use of lavish things is depending on the personal choice indeed, but if we see the other section of society who is struggling for their existence, here the legal and ethical contradiction arises. Indeed, there is no harm to use lavish items, but when ‘one can make the contribution for change in societal curse’ then it should be the obligation to fulfil that. This accentuates that the digital age has thrown a challenge to the society to protect the dignity and respect of the individual as a repercussion of the sharing of the information. The organizations have created a huge business of worth billions of dollars from the already shared individual data. Many multinationals like YouTube, Google Inc. and Facebook etc. are using user access pattern, public posts and their personal information to make huge business through business intelligence and analytics. The idea to have the debate on necessity and desire is really pious to motivate the section of the society to have the sustainable solution for future. This research highlighted the concern to make the user-friendly approach to balance with both the necessity and desire legally in the digital world. The idea has put forward that the use of the advanced technological put the individual in ‘No Choice Zone’ and on the other hand, the desire to use of the same put the individual in a vulnerable position by sharing the individual’s information. The pitfall of the ‘No choice Zone’ taking the individual in the new cyborg era day by day. Therefore, to make the balance between both ideas to make standard aligned protocol in general use and to stop the vulnerable or susceptible use of the human life is need to be identified. The better sustainable use of item digital age ethically and the consequence of the practice of individual information follow fair dealings.